2017
DOI: 10.1097/med.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Maternal epigenetics and fetal and neonatal growth

Abstract: All these investigations continue to provide new insights for improved clinical management of in-utero development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 30 publications
2
53
0
2
Order By: Relevance
“…14 The lack of association between maternal ferritin at 32 weeks gestation and child growth at 36 months of age raises the possibility that robust in utero iron concentrations are most critical in the early stages of pregnancy, for optimal postnatal child growth outcomes. Rapid fetal growth begins from 9 weeks after conception, and poor maternal nutritional status during the first trimester may have a significant impact …”
Section: Bmj Global Healthmentioning
confidence: 99%
“…14 The lack of association between maternal ferritin at 32 weeks gestation and child growth at 36 months of age raises the possibility that robust in utero iron concentrations are most critical in the early stages of pregnancy, for optimal postnatal child growth outcomes. Rapid fetal growth begins from 9 weeks after conception, and poor maternal nutritional status during the first trimester may have a significant impact …”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Several authors have already reported that maternal malnutrition during pregnancy and lactation can be harmful to the birth weight and metabolic homeostasis of the offspring [5][6][7]. Complementarily, few recent studies have demonstrated the association among maternal diet restriction, disturbances in the miRNA expression and metabolic diseases onset in life [6,7].…”
Section: Maternal Under-nutrition and Mirna Expression In Offspringmentioning
confidence: 99%
“…Approximately 2,800 mammalian miRNAs have been annotated and these miRNAs are potentially target up to 60% of protein-coding genes [3]. In addition, disturbances in the miRNA expression are linked to aberrant metabolic changes and onset of diseases [5].…”
Section: Epigenetic Plasticity and Mirna Expressionmentioning
confidence: 99%
See 2 more Smart Citations